A CROSS-CULTURAL STUDY ON THE VALUE STRUCTURE OF MOBILE INTERNET USAGE: COMPARISON BETWEEN INDONESIA AND JAPAN - Wardani, Ranti Yulia; Warsono, Sony (Journal of Indonesian Economy and Business, 2012)
The number of mobile Internet users has been growing rapidly worldwide. Access to the Internet via mobile cellular networks has also grown rapidly. The effects of differentculture of mobile Internet would be interesting to be investigated. The research objective is to investigate the usage pattern differences of mobile Internet users in Indonesia and Japan and to interpret them within the framework of a value structure. The data collection technique used in this study was the survey method. The same questionnaire written in mother language of each country was given to respondents in Japan and Indonesia directly. The result shows that value structures (functional value, emotional value, social value, and monetary value) simultaneously affect the satisfaction of mobile Internet usage of Indonesian respondents, which affect the satisfaction of Japanese respondents. Socialvalue did not significantly affect the satisfaction of mobile Internet usage of Japanese respondents. The implications of cross-cultural differences of mobile Internet will be discussed in this paper. This paper will be ended with discussion, conclusion with practical implications and limitations.Keywords: mobile Internet, cross cultural, m-commerce, Indonesia, Japan.